Semi-analytical methodology for fretting wear evaluation of unlubricated pitch bearing raceways under operative and non-operative periods - D. Cubillas; M. Olave; I. Llavori; I. Ulacia; J. Larrañaga; A. Zurutuza; A. Lopez (Wind Energy Science)
Current methodologies for the evaluation of fretting in pitch bearing raceways only consider damage induced by oscillating control movements. However, pitch bearings can remain static for long operative and non-operative periods, where load fluctuations cause fretting damage due to the small movements and deformations at the contact. In this work a semi-analytical methodology is presented and an analysis of the fretting phenomenon in pitch bearing raceways in the absence of lubricant under both productive and non-productive periods of static pitch control is accomplished. The analysis is performed following the energy-based wear model and the calculation of a total of 30 times series of 10 min of duration concerning winds speeds from 3 to 25 m s−1. As a result, critical locations based on the dissipated energy are identified for the different wind speeds and the contributions of operational and non-operational times, as well as the prediction of damage shapes on the raceway for both cases, are evaluated independently and compared.